2015
DOI: 10.4103/0976-9668.149114
|View full text |Cite
|
Sign up to set email alerts
|

Survey on utility of yoga as an alternative therapy for occupational hazards among dental practioners

Abstract: Background:The therapeutic potential of yoga are often considered complementary to various forms of medical practice. Very few studies have evaluated the effects of yoga in the treatment of occupational hazards among dentists. Hence, this cross-sectional study was designed to evaluate the adoption of yoga techinques as an alternative therapy in treatment of physical and psychological occupational hazards among dental general practitioners in Chennai, India.Materials and Methods:A validated closed-ended questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The common ones include skepticism, cost, lack of time & access to high quality yoga classes and teachers, and stereotypes related to flexibility and athleticism. 16 , 17 In addition, to our knowledge, there haven’t been any yoga-based interventions that have specifically targeted HCPs during the COVID-19 pandemic. One approach that has been posited to address these challenges is Sudarshan Kriya Yoga (SKY).…”
Section: Introductionmentioning
confidence: 99%
“…The common ones include skepticism, cost, lack of time & access to high quality yoga classes and teachers, and stereotypes related to flexibility and athleticism. 16 , 17 In addition, to our knowledge, there haven’t been any yoga-based interventions that have specifically targeted HCPs during the COVID-19 pandemic. One approach that has been posited to address these challenges is Sudarshan Kriya Yoga (SKY).…”
Section: Introductionmentioning
confidence: 99%
“…Stress is notably common in dentists, although only 10% of dentists practice yoga [51]. In this survey study musculoskeletal pain with stress was reported by 47% of the dentists but 53% of the dentists did not consider yoga as an alternative therapy and gave a lack of time as a reason.…”
Section: Dentists and Nursesmentioning
confidence: 97%
“…• More stressed focus less on the maintenance of good oral health. 16 Stressed people have a habit of grinding their teeth resulting in micro-cracks and broken fillings and worn down teeth results in nerve damage; the teeth that are grounded down to the dentin results in sensitivity to heat and cold; gum recession because of pressure on the gum line; loose teeth and gingival pockets due to the motion of teeth grinding; headache and aching jaws because of overworked jaw muscles; and jaw impairment. 9…”
Section: Bad Breathmentioning
confidence: 99%
“…Because of this asana, the blood flow to the lower limbs is reduced, muscles are stretched and these varicose veins are cured. 16…”
Section: Bad Breathmentioning
confidence: 99%